2018
DOI: 10.1371/journal.pone.0202951
|View full text |Cite
|
Sign up to set email alerts
|

Renewable energy consumption and economic growth. Causality relationship in Central and Eastern European countries

Abstract: The new European model stipulates the achievement of an inclusive, sustainable and intelligent economic growth. Increasing the share of renewable energy is one of the factors that improve the quality of economic growth, similar to research, development and investment in human capital. In this paper we tested the correlation between economic growth and renewable energy consumption for ten European Union (EU) member states from Central and Eastern Europe (CEE) in the period 1990–2014, using Auto-regressive and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(96 citation statements)
references
References 56 publications
3
74
0
1
Order By: Relevance
“…Therefore, promoting new energy consumption bears benefits not only for the environment but also for the economic conditions of the countries. Apergis and Payne (2010) [13], Lin and Moubarak (2014) [14], Rafindadi and Ozturk (2017) [15], and Marinas et al (2018) [16] indicated that there is positive bi-directional long run relationship between new energy consumption and economic growth by using data from Organization for Economic Co-operation and Development (OECD) countries, China, Germany, and South Africa, respectively. The bi-directional relationship between new energy consumption and economic growth implied that growing economy is propitious for the development of new energy sector which in turn helps to boost economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, promoting new energy consumption bears benefits not only for the environment but also for the economic conditions of the countries. Apergis and Payne (2010) [13], Lin and Moubarak (2014) [14], Rafindadi and Ozturk (2017) [15], and Marinas et al (2018) [16] indicated that there is positive bi-directional long run relationship between new energy consumption and economic growth by using data from Organization for Economic Co-operation and Development (OECD) countries, China, Germany, and South Africa, respectively. The bi-directional relationship between new energy consumption and economic growth implied that growing economy is propitious for the development of new energy sector which in turn helps to boost economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the study by Marinaș, Dinu, Socol, and Socol (2018), the relationship between economic growth and renewable energy sources in central and eastern Europe was investigated from 1990 to 2014. The results of the study using the ARDL method, both short and long term, determined that there was a significant relationship between the variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, the results revealed a unidirectional causality flowing from renewable energy consumption to economic growth in the longrun. Marinaș, Dinu, Socol and Socol (2018) tested the correlation between economic growth and renewable energy consumption for ten European Union (EU) member states from Central and Eastern Europe (CEE) in the period 1990 to 2014, using Autoregressive and Distributed Lag (ARDL) modeling procedure, a technique that captures causal relationships both on a short run and on a long run. They found that in the short run, the Gross Domestic Product (GDP) and Renewable Energy Consumption (REC) dynamics are independent in Romania and Bulgaria, while in Hungary, Lithuania, and Slovenia an increasing renewable energy consumption improves the economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%